3D Nonlinear Parallel FEM for Analyzing Dynamic Response of the Large- Scale Saturated Soil Layers-Civil Structures Interaction Problem (Part II: Validation and Performance) - Jafril Tanjung (Institut Teknologi Bandung, 2010)
Abstract. In this second paper, a validation and performance of the nonlinear parallel FEM proposed in the first paper are evaluated. An experimental model for investigating a seismic earth pressure has been simulated for numerically validation purpose. The numerical results for the seismic active earth pressure parameters and dynamic pore water pressure acting on the wall coincide well with those of the experiment. The efficiency of the parallel computation was made clear by the comparison of the executing time for the different size of models. The results in this numerical analysis suggests the relation between the seismic active earth pressure and the dynamic pore water pressure acting on the wall for a saturated soil layer.Abstrak. Dalam makalah kedua ini akan dievaluasi keabsahan dan kinerja paralel elemen hingga non-linier yang dijabarkan dalam makalah pertama. Untuk maksud tersebut, model eksperimental untuk menganalisis perilaku seismik tekanan tanah, telah disimulasikan. Hasil analisis numerik menunjukkan bahwa nilai parameter seismik untuk tekanan tanah dan tekanan dinamik air pori yang bekerja pada dinding penahan tanah, sesuai dengan yang diamati dalam pengujian laboratorium. Efisiensi komputasi secara paralel ditunjukkan dengan membandingkan waktu yang diperlukan untuk menganalisis beberapa model dengan ukuran yang berbeda. Hasil analisis juga memberi gambaran tentang hubungan antara tekanan seismic tanah dan tekanan air pori yang bekerja pada dinding penahan lapisan tanah jenuh.